2017
DOI: 10.3748/wjg.v23.i47.8300
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in oxidative pathway related genes and susceptibility to inflammatory bowel disease

Abstract: AIMTo investigate whether common variants in the oxidative pathway genes influence inflammatory bowel disease (IBD) risk among Moroccan patients.METHODSThe distribution of (TAAA)n_rs12720460 and (CCTTT)n _rs3833912 NOS2A microsatellite repeats, HIF-1A_rs11549467 and NFKB1-94ins/delATTG_rs28362491 was analyzed in 507 subjects grouped in 199 IBD and 308 healthy controls. Genotyping was performed with polymerase chain reaction-fluorescent method and the TaqMan® allelic discrimination technology.RESULTSThe allele … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…NOS2 encodes the synthesis of inducible nitric oxide synthase (iNOS). The highly expressed iNOS in the inflamed mucosa plays a key role in oxidative stress-induced inflammation [ 23 ]. NOS activity in colon biopsies has been shown to be correlated with disease intensity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOS2 encodes the synthesis of inducible nitric oxide synthase (iNOS). The highly expressed iNOS in the inflamed mucosa plays a key role in oxidative stress-induced inflammation [ 23 ]. NOS activity in colon biopsies has been shown to be correlated with disease intensity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants within the NOS2 gene have been associated with IBD susceptibility in different populations (Martín et al, 2007;Senhaji et al, 2017), and increased mRNA levels were found in the colonic mucosa of patients with active UC, compared to patients with inactive UC and controls, and in CD patients compared to controls (Coburn et al, 2016). Recently, Luther and collaborators found that colonic expression of NOS2 was elevated in patients with loss of response to TNFα-antagonist compared to responders (Luther et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The association of diabetic complication risk was also supported by a previous meta-analysis report [ 75 ]. Also the subgroup analysis results of HIF1A 1772 C/T polymorphism showed insignificant association with autoimmune diseases, inflammatory diseases, and preeclampsia under all five genetic models which goes in favor of Wipff et al [ 31 ] and Feng et al [ 25 ] for autoimmune disease, Torres et al [ 27 ], Chachami et al [ 32 ] and Senhaji et al [ 41 ] for inflammatory disease, and Nava-Salazar et al [ 34 ] for preeclampsia. The subgroup analysis results of HIF1A 1790 G/A polymorphism showed significant association with CVD under homozygote model ( AA vs. GG ) and diabetic complications under allelic ( A vs. G ) and homozygote ( AA vs. GG ) models.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, some authors showed the significant association of HIF1A (1772 C/T and 1790 G/A) with cardiovascular diseases (CVD) [ 21 , 40 ], though some authors did not find the significant effect in the same question [ 22 , 26 ]. Again for inflammatory diseases, a significant association was claimed by [ 20 , 38 ], and an insignificant association by [ 27 , 32 , 41 ]. For Chronic obstructive pulmonary disease (COPD), Yu et al [ 17 ] and Putra et al [ 39 ] claimed the significant and insignificant association with HIF1A gene polymorphisms, respectively.…”
Section: Introductionmentioning
confidence: 99%